Perovskite solar cell and preparation method thereof
By introducing trivalent iron compounds into the electron transport layer of perovskite solar cells, the problem of insufficient photoelectric performance and efficiency of existing perovskite solar cells is solved, and higher photoelectric performance and efficiency are achieved.
Patent Information
- Application Number
- CN202311008670.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-08-10
AI Technical Summary
The photoelectric performance and efficiency of existing perovskite solar cells still need to be improved, mainly due to the insufficient performance of the electron transport layer, resulting in low extraction and transmission efficiency of photogenerated electrons.
The electron transport layer of perovskite solar cells is introduced into the electron transport layer, which is doped with Fe3+ ions, and the performance of the electron transport layer is optimized. The specific method includes forming a dense electron transport layer and a mesoporous electron transport layer on the transparent conductive layer and introducing a trivalent iron compound into the dense electron transport layer.
By introducing trivalent iron compounds, the performance of the electron transport layer is optimized and the photoelectric performance and efficiency of perovskite solar cells are improved, including improving open circuit voltage and photoelectric conversion.
Smart Images

Figure CN119486450A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solar cells, and in particular to a perovskite solar cell and a preparation method thereof. Background Art
[0002] In recent years, perovskite solar cells have attracted extensive attention due to the advantages of perovskite materials such as long carrier diffusion length, adjustable band gap, high light absorption coefficient and low raw material cost. For example, halide perovskite solar cells are considered to be the third generation of solar cells, and the efficiency of single-junction lead-based perovskite solar cells is comparable to that of silicon-based solar cells. However, the optoelectronic performance and efficiency of existing perovskite solar cells still need to be improved. Summary of the invention
[0003] The present invention provides a perovskite solar cell and a preparation method thereof, which can improve the photoelectric performance and efficiency of the perovskite solar cell.
[0004] In one aspect of the present invention, a perovskite solar cell is provided, comprising a transparent conductive layer, an electron transport layer, a perovskite light absorbing layer and a hole transport layer stacked in sequence, wherein the electron transport layer comprises titanium dioxide and a trivalent iron compound.
[0005] According to one embodiment of the present invention, the electron transport layer includes a dense electron transport layer and a mesoporous electron transport layer located between the dense electron transport layer and the perovskite light absorbing layer, and the trivalent iron compound exists in the dense electron transport layer.
[0006] According to one embodiment of the present invention, in the dense electron transport layer, the molar ratio of iron element to titanium element is 1:(300-650).
[0007] According to one embodiment of the present invention, the transparent conductive layer includes FTO conductive glass.
[0008] Another aspect of the present invention provides a method for preparing the above-mentioned perovskite solar cell, comprising the following steps: applying a first mixed solution containing an organic titanium source, an iron source for forming the trivalent iron compound and a first solvent on a transparent conductive layer to form a dense electron transport layer; applying a second mixed solution containing an inorganic titanium source and a second solvent on the dense electron transport layer to form a mesoporous electron transport layer; and sequentially forming a perovskite light absorption layer and a hole transport layer on the mesoporous electron transport layer to obtain the perovskite solar cell.
[0009] According to one embodiment of the present invention, before applying the first mixed liquid on the transparent conductive layer, the transparent conductive layer is pretreated, and the pretreatment process includes: cleaning the transparent conductive layer with a cleaning agent, drying it, and then performing ultraviolet ozone treatment; wherein the cleaning agent includes one or more of water, acetone, isopropyl alcohol, ethanol, and glass cleaning agent.
[0010] According to one embodiment of the present invention, the organic titanium source includes diisopropoxy diacetylacetonate titanium; and / or the iron source includes acetylacetonate iron; and / or the molar ratio of the iron element in the iron source to the titanium element in the organic titanium source is 1:(300-650); and / or the first solvent includes n-butanol.
[0011] According to one embodiment of the present invention, the organic titanium source includes diisopropoxy diacetylacetonate titanium, and the iron source includes ferric acetylacetonate. The formation process of the first mixed liquid includes: mixing the diisopropoxy diacetylacetonate titanium and the ferric acetylacetonate, and then adding a first solvent to the obtained mixed liquid to obtain the first mixed liquid; wherein the volume ratio of the mixed liquid to the first solvent is 1:14 to 18.
[0012] According to one embodiment of the present invention, the first mixed solution is spin-coated on the transparent conductive layer by a dynamic spin coating method, and then annealed at 110-130° C. for 8-12 min to form the dense electron transport layer.
[0013] According to one embodiment of the present invention, the inorganic titanium source includes titanium dioxide; and / or, the second solvent includes ethanol; and / or, the second mixed liquid is spin-coated on the dense electron transport layer by static spin coating, and then annealed at 450-550°C for 40-70 minutes to form the mesoporous electron transport layer.
[0014] In the present invention, a trivalent iron compound is introduced into the electron transport layer of the perovskite solar cell, so that the electron transport layer is doped with trivalent iron ions (Fe 3+ ), the performance of the electron transport layer can be optimized, thereby improving the photoelectric performance and efficiency of the perovskite solar cell. In addition, the perovskite solar cell of the present invention also has the advantages of simple preparation process and easy operation, which is conducive to practical industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 A schematic diagram of the structure of a perovskite solar cell according to an embodiment of the present invention;
[0016] Figure 2Steady-state photoluminescence spectra of the perovskite solar cells of Example 1 and Comparative Example 1 (the abscissa is wavelength (Wavelength), and the ordinate is photoluminescence intensity (PLintensity)));
[0017] Figure 3 The transient photoluminescence spectra of the perovskite solar cells of Example 1 and Comparative Example 1 (the abscissa is time (Time), and the ordinate is normalized photoluminescence intensity (Normalized PL intensity));
[0018] Figure 4 This is a physical picture (photo) of the perovskite solar cell prepared in Example 1.
[0019] Explanation of the reference numerals: 1: transparent conductive layer; 11: first region; 12: second region; 2: electron transport layer; 21: dense electron transport layer; 22: mesoporous electron transport layer; 3: perovskite light absorbing layer; 4: hole transport layer; 5: counter electrode. DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0021] In recent years, perovskite solar cells have attracted extensive attention due to their advantages such as long carrier diffusion length, adjustable band gap, high light absorption coefficient and low raw material cost. However, the photoelectric performance and efficiency of existing perovskite solar cells still need to be improved.
[0022] For example, the main functional layers of perovskite solar cells include electron transport layer, perovskite light absorption layer and hole transport layer, which is also called a "sandwich" structure. The electron transport layer can reduce the potential barrier between the electrode and the perovskite, promote the migration of carriers, and effectively block holes, thereby inhibiting the recombination of electrons and holes at the interface. It is crucial for efficient and stable perovskite solar cells. In the formal structure and the trans structure, the electron transport layer materials usually include titanium dioxide (TiO2), tin dioxide (SnO2), PCBM, etc. Among them, TiO2 is a commonly used electron transport layer material in mesoporous nip-type perovskite solar cells. Pure TiO2 has problems such as large bandgap width, low electron mobility, and easy degradation under ultraviolet light. At the same time, there are also some defects in the process of preparing dense electron transport layers by dynamic spin coating and other methods, such as oxygen vacancy defects. The presence of oxygen vacancy defects will cause the two Ti around it to 4+ Become Ti 3+ , thereby capturing the photogenerated electrons produced by the perovskite light-absorbing layer, which has an adverse effect on the photoelectric conversion efficiency and stability of the battery device.
[0023] In view of this, an embodiment of the present invention provides a perovskite solar cell, such as Figure 1 As shown, the perovskite solar cell includes a transparent conductive layer 1, an electron transport layer 2, a perovskite light absorption layer (perovskite thin film layer) and a hole transport layer 4 which are stacked in sequence, and the electron transport layer 2 includes TiO2 and a trivalent iron compound.
[0024] In the embodiment of the present invention, based on the properties of the electron transport layer 2 in the perovskite solar cell, a trivalent iron compound is introduced into the electron transport layer 2 to make the electron transport layer 2 doped with Fe. 3+ , optimize the performance of the electron transport layer 2, thereby improving the photoelectric performance and efficiency of the perovskite solar cell, for example, the open circuit voltage and photoelectric conversion rate of the perovskite solar cell can be effectively improved.
[0025] According to the research and analysis of the inventor, based on Fe 3+ With Ti 4+ Similar ionic radius and other properties, Fe 3+ can diffuse into the TiO2 lattice, therefore, by doping Fe in the electron transport layer 2 containing TiO2 3+ , which can effectively promote the extraction and transmission of photogenerated electrons, thereby improving the photoelectric conversion efficiency and other performance of perovskite solar cells. Therefore, by introducing trivalent iron compounds into the electron transport layer 2, the charge transfer between the electron transport layer 2 and the perovskite light absorption layer 3 can be promoted, the fluorescence quenching effect can be enhanced, and the photoelectric performance and efficiency of the perovskite solar cell can be improved.
[0026] After further research, it was found that the above-mentioned trivalent iron compound may include iron acetylacetonate, which is more conducive to cooperating with TiO2, optimizing the performance of the electron transport layer 2, and further improving the photoelectric performance and efficiency of the perovskite solar cell.
[0027] Generally, the electron transport layer 2 may be a titanium dioxide layer, that is, TiO2 forms a matrix of the electron transport layer 2, and the trivalent iron compound is dispersed in the matrix.
[0028] Continue to refer Figure 1 The electron transport layer 2 may include a dense electron transport layer 21 (dense thin film layer), and a mesoporous electron transport layer 22 (mesoporous thin film layer) located between the dense electron transport layer 21 and the perovskite light absorption layer 3 .
[0029] Specifically, the above-mentioned dense electron transport layer 21 and mesoporous electron transport layer 22 can both include TiO2, respectively. Further, the dense electron transport layer 21 and the mesoporous electron transport layer 22 can both be titanium dioxide layers, that is, the dense electron transport layer 21 is a dense titanium dioxide layer (c-TiO2), and the mesoporous electron transport layer 22 is a mesoporous titanium dioxide layer (m-TiO2).
[0030] In some embodiments, a trivalent iron compound exists in the dense electron transport layer 21, that is, the dense electron transport layer 21 of the embodiment of the present invention is a dense electron transport layer 21 doped with trivalent iron ions, which is beneficial to further optimize the performance of the electron transport layer 2 and improve the photoelectric performance and efficiency of the perovskite solar cell.
[0031] Specifically, according to the research of the present invention, on the one hand, the introduction of trivalent iron compounds into the dense electron transport layer 21 is conducive to the performance of its charge transport function; on the other hand, in the process of preparing the dense electron transport layer 21 by dynamic spin coating and other methods, there are defects such as oxygen vacancy defects, among which the presence of oxygen vacancy defects will cause the two Ti 4+ Become Ti 3+ , thereby capturing the photogenerated electrons generated by the perovskite light absorption layer 3, which has an adverse effect on the photoelectric conversion efficiency and stability of the battery device. By introducing a trivalent iron compound into the dense electron transport layer 21, the dense electron transport layer 21 is doped with Fe 3+ , which can effectively overcome these problems, thereby optimizing the performance of the dense electron transport layer 21, and further improving the photoelectric performance and efficiency of perovskite solar cells.
[0032] Specifically, in the above-mentioned dense electron transport layer 21, the molar ratio of iron element to titanium element is 1:(300-650) (that is, the molar ratio of trivalent iron compound to titanium dioxide is 1:(300-650) based on iron element and titanium element), for example, 1:300, 1:330, 1:350, 1:380, 1:400, 1:430, 1:450, 1:480, 1:500, 1:530, 1:550, 1:580, 1:600, 1:630, 1:650 or a range consisting of any two of them.
[0033] In the present invention, the mesoporous electron transport layer 22 can have the mesoporous morphology and structure of a conventional mesoporous electron transport layer 22 in the art, and the dense electron transport layer 21 can have the dense morphology and structure of a conventional dense electron transport layer 21 in the art, without any particular limitation.
[0034] In addition, the transparent conductive layer 1 is formed of a transparent conductive material, which may specifically include transparent conductive glass. In some preferred embodiments, the transparent conductive layer 1 may include FTO (fluorine-doped tin oxide) conductive glass.
[0035] In addition, the above-mentioned perovskite absorption layer may include metal halide and / or organic halide, the metal halide may include metal iodide, for example, lead iodide; the organic halide may include organic iodide and / or organic chloride, for example, iodomethane and / or chloromethylamine, etc., but is not limited thereto.
[0036] In addition, the hole transport layer 4 includes a hole transport material. For example, the hole transport layer 4 is a Spiro-OMeTAD hole transport layer 4 formed of Spiro-OMeTAD.
[0037] In general, if Figure 1 As shown, the perovskite solar cell further comprises a counter electrode 5, which may comprise a metal, for example, a metal electrode formed of a metal, and the metal comprises, for example, gold (Au).
[0038] Continue to refer Figure 1 The side of the transparent conductive layer 1 facing the perovskite light absorbing layer 3 includes a first region 11 and a second region 12 (or conductive region), the electron transport layer 2, the perovskite light absorbing layer 3 and the hole transport layer 4 are sequentially stacked in the first region 11 of the transparent conductive layer 1, that is, the first region 11 is covered by these layers, and the second region 12 is not covered by these layers, wherein a counter electrode 5 is respectively provided on a side of the hole transport layer 4 facing away from the perovskite light absorbing layer 3 and on the second region 12. Specifically, as Figure 1 what Figure 4 As shown, the counter electrode 5 has multiple (such as Figure 1 As shown, the number of electrodes 5 is 7; or Figure 4 As shown, the number of counter electrodes 5 is 9), wherein one counter electrode 5 is arranged in the second area 12 of the transparent conductive layer 1, and the remaining counter electrodes 5 are arranged on the side of the hole transport layer 4 away from the perovskite light absorption layer 3. These counter electrodes 5 can be specifically evenly distributed on the side of the hole transport layer 4 away from the perovskite light absorption layer 3, for example, distributed in an array on the side of the hole transport layer 4 away from the perovskite light absorption layer 3.
[0039] The present invention also provides a method for preparing the above-mentioned perovskite solar cell, which comprises the following steps:
[0040] S1. Pre-treating the transparent conductive layer 1. The pre-treating process includes: cleaning the transparent conductive layer 1 with a cleaning agent, drying it, and then performing ultraviolet ozone treatment; wherein the cleaning agent includes one or more of water, acetone, isopropyl alcohol, ethanol, and glass cleaning agent.
[0041] The glass cleaning agent may be a conventional glass cleaning agent in the art, which includes, for example, a surfactant and water, and may be commercially available or homemade according to a conventional method in the art, and is not particularly limited thereto.
[0042] In specific implementation, a variety of cleaning agents can be used to ultrasonically clean the transparent conductive layer 1 (such as FTO conductive glass) in sequence, for example, water, glass cleaning agent, isopropanol, ethanol and water are used to ultrasonically clean the transparent conductive layer 1 in sequence (the mass ratio of glass cleaning agent to water is, for example, about 1:3), or acetone, isopropanol, ethanol and water are used to ultrasonically clean the transparent conductive layer 1 in sequence, and the cleaning time each time can be 20 to 40 minutes, for example, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes or a range composed of any two thereof, and then placed in a drying equipment such as an oven for drying (drying), and the drying temperature can be 110 to 130°C, for example, 110°C, 115°C, 120°C, 125°C, 130°C or a range composed of any two thereof, so as to remove impurities and moisture on the surface of the transparent conductive layer 1, and then perform ultraviolet ozone treatment.
[0043] The water used may specifically include deionized water.
[0044] The time of the ultraviolet ozone treatment can be 20 to 40 minutes, for example, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes or a range consisting of any two of them.
[0045] In the above process, the organic matter on the surface of the transparent conductive layer 1 can be oxidized and degraded by ultraviolet ozone treatment, and the work function of the surface of the transparent conductive layer 1 can be enhanced, which is beneficial to electron transmission.
[0046] The embodiment of the present invention may use a UV-ozone generator or other conventional device in the art to perform UV-ozone treatment, and there is no particular limitation on this.
[0047] S2 . Apply a first mixed solution containing an organic titanium source, an iron source for forming the above-mentioned trivalent iron compound, and a first solvent on the transparent conductive layer 1 to form a dense electron transport layer 21 .
[0048] Specifically, the first mixed liquid can be spin-coated on the transparent conductive layer 1 by a dynamic spin coating method. Specifically, the first mixed liquid can be spin-coated on the transparent conductive layer 1 at a rotation speed of 1500 to 2500 rpm (the rotation speed can be 1500 rpm, 1600 rpm, 1700 rpm, 1800 rpm, 1900 rpm, 2000 rpm, 2100 rpm, 2200 rpm, 23000 rpm, 2400 rpm, 2500 rpm or a range composed of any two of them), and then after a first drying treatment, a dense electron transport layer 21 is formed.
[0049] Among them, the first drying treatment can specifically include annealing treatment, the temperature of which can be 110-130°C, for example, 110°C, 115°C, 120°C, 125°C, 130°C or a range consisting of any two thereof, and the time can be 8-12min, for example, 8min, 9min, 10min, 11min, 12min or a range consisting of any two thereof.
[0050] In some embodiments, the first mixed solution is spin-coated on the transparent conductive layer 1 by a dynamic spin coating method, and then annealed at 110-130° C. for 8-12 min to form a dense electron transport layer 21 .
[0051] In the above process, after the first drying treatment, the organic titanium source is converted into TiO2, that is, the formed dense electron transport layer 21 is a dense titanium dioxide layer, and the iron source forms a trivalent iron compound dispersed in the dense electron transport layer 21, so that the dense electron transport layer 21 is doped with trivalent iron ions.
[0052] Specifically, the organic titanium source may include diisopropoxytitanium bisacetylacetonate.
[0053] In addition, the iron source may include an organic iron source, in which the iron element may be trivalent. It is generally preferred that the iron source includes ferric acetylacetonate.
[0054] In addition, the amount of iron source is controlled as follows: the molar ratio of the iron element in the iron source to the titanium element in the organic titanium source is 1:(300-650). By adding a low concentration of iron source, an appropriate amount of trivalent iron ions is introduced into the dense electron transport layer 21 (in the dense electron transport layer 21, the molar ratio of the iron element to the titanium element is 1:(300-650)), which can further optimize the performance of the dense electron transport layer 21, thereby further improving the photoelectric performance and efficiency of the perovskite solar cell.
[0055] In a specific implementation, the organic titanium source and the iron source can be mixed, and then the first solvent is added to the obtained mixture, and the mixture is mixed evenly by stirring, for example, stirring for 50 to 70 minutes to obtain the first mixed solution.
[0056] In some preferred embodiments, the formation process of the above-mentioned first mixed liquid includes: mixing diisopropoxy diacetylacetonate titanium and acetylacetonate iron, and then adding a first solvent to the obtained mixed liquid to obtain a first mixed liquid; wherein the volume ratio of the mixed liquid to the first solvent can be 1:(14~18), for example, 1:14, 1:14.5, 1:15, 1:15.5, 1:16, 1:16.5, 1:17, 1:17.5, 1:18 or a range consisting of any two of them.
[0057] In addition, the first solvent may include n-butanol, and specifically anhydrous n-butanol may be used.
[0058] According to the inventor's research, in the above-mentioned preparation process, diisopropoxy diacetylacetonate titanium, acetylacetonate iron and n-butanol are used, and a dense electron transport layer 21 doped with trivalent iron ions is prepared by a dynamic spin coating method, which is beneficial to further improve the properties of the dense electron transport layer 21 such as conductivity and electron mobility, promote the charge transfer between the electron transport layer 2 and the perovskite light absorbing layer 3, and enhance the fluorescence quenching effect, thereby further improving the photoelectric performance and efficiency of the perovskite solar cell.
[0059] In a specific implementation, the organic titanium source and the iron source can be placed in a glass bottle and mixed, and then the first solvent is added thereto and mixed evenly to obtain a first mixed liquid; the first mixed liquid is then coated on the transparent conductive layer 1. After the coating is completed, the film material on the second area 12 of the transparent conductive layer 1 is removed. Specifically, a cotton swab soaked in isopropyl alcohol can be used to scrape off the film material on the second area 12 to expose the second area 12 of the transparent conductive layer 1; the transparent conductive layer 1 coated with the first mixed liquid is then placed on a flat heating table or other equipment for heating to perform a first drying treatment to form a dense electron transport layer 21.
[0060] S3 , coating a second mixed solution containing an inorganic titanium source and a second solvent on the dense electron transport layer 21 to form a mesoporous electron transport layer 22 .
[0061] Specifically, the second mixed liquid can be spin-coated on the dense electron transport layer 21 by a static spin coating method. Specifically, the second mixed liquid can be spin-coated on the dense electron transport layer 21 at a rotation speed of 5500 to 6500 rpm (the rotation speed is, for example, 5500 rpm, 5700 rpm, 5900 rpm, 6000 rpm, 6200 rpm, 6400 rpm, 6500 rpm or a range composed of any two of them), and then after a second drying treatment, the mesoporous electron transport layer 22 is formed.
[0062] Among them, the second drying treatment can specifically include annealing treatment, the temperature of which can be 450-550°C, for example, 450°C, 470°C, 490°C, 500°C, 520°C, 540°C, 550°C or a range consisting of any two thereof, and the time can be 40-70min, for example, 40min, 45min, 50min, 55min, 60min, 65min, 70min or a range consisting of any two thereof.
[0063] In some embodiments, the second mixed solution is spin-coated on the dense electron transport layer 21 by static spin coating, and then annealed at 450-550° C. for 40-70 min to form the mesoporous electron transport layer 22 .
[0064] In a specific implementation, the inorganic titanium source and the second solvent can be placed in a glass bottle and stirred thoroughly. For example, a magnet is added thereto for magnetic stirring. The stirring time can be specifically 20 to 30 hours. The obtained mixed solution is the second mixed solution. The second mixed solution is then coated on the side of the dense electron transport layer 21 facing away from the transparent conductive layer 1. After the coating is completed, the film layer material on the second area 12 of the transparent conductive layer 1 is removed. Specifically, a cotton swab soaked in isopropyl alcohol can be used to scrape off the film layer material on the second area 12 to expose the second area 12 of the transparent conductive layer 1. Subsequently, the entire substrate (including the transparent conductive layer 1, the dense electron transport layer 21 formed on the transparent conductive layer 1, and the second mixed solution coated on the dense electron transport layer 21) is placed on a flat heating table and other equipment for heating to perform a second drying treatment to form a mesoporous electron transport layer 22.
[0065] Specifically, the inorganic titanium source may include TiO2, and a mesoporous titanium dioxide layer (ie, the mesoporous titanium dioxide electron transport layer 2) is formed through the above process.
[0066] Additionally, the second solvent may include ethanol.
[0067] In addition, the mass ratio of the inorganic titanium source to the second solvent may be 1:(7-9), for example, 1:7, 1:7.5, 1:8, 1:8.5, 1:9 or a range consisting of any two thereof.
[0068] S4, forming a perovskite light absorption layer 3 on the mesoporous electron transport layer 22.
[0069] Specifically, the perovskite light absorbing layer 3 is formed on the side of the mesoporous electron transport layer 22 away from the dense electron transport layer 21. In the specific implementation, the material used to form the perovskite light absorbing layer 3 (such as the aforementioned metal halide and / or organic halide, etc.) can be mixed with the third solvent, and after sufficient stirring (the stirring time can be specifically 4 to 5 hours), a perovskite precursor solution is obtained; the perovskite precursor solution is spin-coated on the mesoporous electron transport layer 22, specifically, the spin coating can be performed at a rotation speed of 3500 to 4500 rpm (the rotation speed is, for example, 3500 rpm, 3700 rpm, 3900 rpm, 4000 rpm, 4200 rpm, 4400 rpm, 4500 rpm or a range composed of any two thereof), and an anti-solvent is dripped on the wet film formed on the mesoporous electron transport layer 22 (specifically, the anti-solvent can be dripped about 20 seconds before the end of spin coating). After the spin coating is completed, annealing is performed to form the perovskite light absorbing layer 3.
[0070] The annealing process may include step annealing, i.e., at least two annealing processes are performed, the annealing temperature increases successively, the annealing time may also increase successively, or the time of each annealing process is substantially the same. By performing at least two annealing processes, annealing may be performed at a lower temperature first, so that the solvent evaporates more slowly to grow larger perovskite grains, thereby facilitating the optimization of the photoelectric effect of the perovskite solar cell, and then annealing may be performed at a higher temperature to fully remove the solvent.
[0071] In some specific embodiments, the annealing process includes sequentially performing a first annealing treatment and a second annealing treatment. The temperature of the first annealing treatment can be 110-120°C and the time can be 3-5 minutes. The temperature of the second annealing treatment can be 140-160°C and the time can be 5-10 minutes. That is, the sample after spin coating is annealed at 110-120°C for 3-5 minutes, and then annealed at 140-160°C for 5-10 minutes to form a perovskite light absorbing layer.
[0072] The third solvent may include dimethyl sulfoxide (DMSO) and / or dimethylformamide (DMF), preferably a mixed solvent of DMSO and DMF, and the anti-solvent may include diethyl ether.
[0073] S5 , forming a hole transport layer 4 on the perovskite light absorption layer 3 .
[0074] Specifically, the hole transport layer 4 is formed on the side of the perovskite light absorbing layer 3 facing away from the mesoporous electron transport layer 22, which can be formed by conventional methods in the art such as spin coating, for example, by spin coating Spiro-OMeTAD on the perovskite light absorbing layer 3, and after oxidation for 10 to 14 hours, a Spiro-OMeTAD hole transport layer 4 is formed.
[0075] After the spin coating is completed, the film material on the second area 12 of the transparent conductive layer 1 is removed. Specifically, a cotton swab soaked with γ-hydroxybutyrolactone (GBL) can be used to scrape off the film material on the second area 12 to expose the second area 12 of the transparent conductive layer 1.
[0076] S6: forming a counter electrode 5 on the second region 12 of the transparent conductive layer 1 and the hole transport layer 4 to produce a perovskite solar cell.
[0077] Specifically, the counter electrode 5 can be formed by vacuum evaporation, for example, Au electrode can be formed by vacuum evaporation. In specific implementation, vacuum evaporation can be performed by conventional evaporation devices in the art such as vacuum coating apparatus to form the counter electrode 5, thereby manufacturing a battery device (i.e., a perovskite solar cell).
[0078] The present invention is further described below through specific examples and comparative examples.
[0079] Example 1
[0080] S1. Pretreatment of FTO conductive glass
[0081] The FTO conductive glass was ultrasonically cleaned with acetone, isopropanol, ethanol, and deionized water in sequence, with each cleaning time being 30 minutes.
[0082] Then the FTO conductive glass was placed in an oven and dried at 120°C;
[0083] The dried FTO conductive glass was treated with UV-ozone for 30 min;
[0084] S2. Formation of a dense electron transport layer
[0085] Add ferric acetylacetonate (the amount of ferric acetylacetonate added satisfies the molar ratio of iron element to titanium element shown in Table 1) to 2 mL of diisopropoxydiacetylacetonato titanium (diisopropoxydiacetylacetonato titanium from Alfa, 75% isopropanol solution) to obtain a mixed solution A (in the mixed solution A, the molar ratio of ferric acetylacetonate to diisopropoxydiacetylacetonato titanium is 1:75 (that is, the molar ratio of iron element in ferric acetylacetonate to titanium element in diisopropoxydiacetylacetonato titanium is 1:75));
[0086] 0.1 mL of the mixed solution A was added to 0.7 mL of diisopropoxy titanium bisacetylacetonate to obtain a mixed solution B (in the mixed solution B, the molar ratio of ferric acetylacetonate to diisopropoxy titanium bisacetylacetonate was 1:600);
[0087] Add 0.1 mL of mixed solution B to 1.6 mL of anhydrous n-butanol and shake well to obtain a first mixed solution;
[0088] The first mixed solution was spin-coated on the FTO conductive glass at a rotation speed of 2000 rpm by a dynamic spin coating method, and then annealed at 120° C. for 10 min to form a dense electron transport layer;
[0089] S3. Formation of Mesoporous Electron Transport Layer
[0090] Titanium dioxide and anhydrous ethanol were mixed in a mass ratio of 1:8 and stirred for 12 hours to obtain a second mixed solution;
[0091] The second mixed solution was spin-coated on the dense electron transport layer at a rotation speed of 6000 rpm by a static spin coating method, and then annealed at 500° C. for 50 min to form a mesoporous electron transport layer;
[0092] S4. Formation of perovskite light-absorbing layer
[0093] Iodoformamidine, lead iodide, and chloromethylamine were placed in a mixed solvent of dimethyl sulfoxide and dimethylformamide and stirred for 6 hours to obtain a perovskite precursor solution;
[0094] The perovskite precursor solution was spin-coated on the mesoporous electron transport layer at a rotation speed of 4000 rpm, and ether (anti-solvent) was added dropwise 20 seconds before the spin coating was stopped. After the spin coating was completed, the solution was first annealed at 120°C for 5 minutes (the first stage annealing treatment), and then step-annealed at 150°C for 5 minutes (the second stage annealing treatment) to form a perovskite light absorption layer;
[0095] S5. Formation of hole transport layer
[0096] Spiro-OMeTAD was spin-coated on the perovskite light-absorbing layer and oxidized for 12 h to form a hole transport layer;
[0097] S6. Formation of Counter Electrode
[0098] A vacuum coating apparatus was used for vacuum evaporation to form an Au electrode (i.e., a counter electrode) on the side of the hole transport layer away from the perovskite light absorbing layer and the second region of the FTO conductive glass (i.e., the exposed conductive region) to obtain a perovskite solar cell ( Figure 4 1 shows different batches of perovskite solar cells made according to the process of Example 1).
[0099] Comparative Example 1: The difference from Example 1 is that in step S2, 150 μL of diisopropoxy diacetylacetonate titanium and 2.4 mL of anhydrous n-butanol are mixed and shaken to obtain a first mixed solution (i.e., no acetylacetonate iron is added in step S2 of Comparative Example 1), and the other conditions are the same as in Example 1.
[0100] Embodiment 2 to Embodiment 5: The difference from Embodiment 1 is that in step S2, the amount of ferric acetylacetonate used is different (i.e., the content of trivalent iron compound in the dense electron transport layer formed is different), as shown in Table 1. Except for the differences shown in Table 1, the other conditions are the same as those in Embodiment 1.
[0101] Example 6: The difference from Example 1 is that the formed dense electron transport layer is not doped with a trivalent iron compound, and the mesoporous electron transport layer is doped with a trivalent iron compound. The difference in the preparation process is as follows:
[0102] (1) No ferric acetylacetonate is added in step S2 (i.e., 150 μL of diisopropoxy diacetylacetonate titanium and 2.4 mL of anhydrous n-butanol are mixed and shaken to obtain a first mixed solution);
[0103] (2) adding ferric acetylacetonate in step S3 (i.e., mixing titanium dioxide and anhydrous ethanol in a mass ratio of 1:8, and then adding ferric acetylacetonate thereto;
[0104] The remaining conditions are the same as those in Example 1.
[0105] The open circuit voltage (Voc), current density (Jsc), fill factor (FF) and power conversion efficiency (PCE) of the perovskite solar cells of each embodiment and comparative example were measured as follows: Figure 1 shown.
[0106] Table 1
[0107]
[0108] *: The amount of ferric acetylacetonate in Table 1 is the molar ratio of the iron element to the titanium element (i.e., the molar ratio of ferric acetylacetonate to the titanium source used, calculated on the basis of the iron element and the titanium element).
[0109] It can be seen that, relative to Comparative Example 1, trivalent iron compounds are introduced into the electron transport layers of Examples 1 to 7, that is, the electron transport layers are doped with trivalent iron ions, so that the perovskite solar cells have higher open circuit voltage, fill factor and energy conversion efficiency (photoelectric conversion efficiency), thereby improving the photoelectric performance and efficiency of the perovskite solar cells.
[0110] Among them, relative to Example 2 and Example 5, the amount of ferric acetylacetonate used in Example 1, Example 3 and Example 4 is within a more suitable range, so that the formed dense electron transport layer is doped with a more suitable content of trivalent iron ions, thereby making the perovskite solar cell exhibit more excellent photoelectric performance and efficiency.
[0111] Compared with Example 6, Example 1 introduces a trivalent iron compound into the dense electron transport layer, showing more excellent photoelectric performance and efficiency.
[0112] In addition, the steady-state photoluminescence spectra of the perovskite solar cells of Example 1 and Comparative Example 1 are shown in Figure 2 , transient photoluminescence spectrum is shown in Figure 3 This further illustrates that by introducing trivalent iron compounds into the electron transport layer so that the electron transport layer is doped with trivalent iron ions, the photoelectric performance and efficiency of perovskite solar cells can be effectively improved.
[0113] In the description of the present invention, terms such as "first" and "second" are used only for descriptive purposes, such as distinguishing between components to more clearly illustrate / explain the technical solution, and cannot be understood as indicating or implying the number of the indicated technical features or the order with substantial significance.
[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A perovskite solar cell, characterized in that: The invention comprises a transparent conductive layer, an electron transport layer, a perovskite light absorption layer and a hole transport layer which are stacked in sequence, wherein the electron transport layer comprises titanium dioxide and a trivalent iron compound.
2. The perovskite solar cell according to claim 1, characterized in that The electron transport layer includes a dense electron transport layer and a mesoporous electron transport layer located between the dense electron transport layer and the perovskite light absorption layer, and the trivalent iron compound exists in the dense electron transport layer.
3. The perovskite solar cell according to claim 2, characterized in that: In the dense electron transport layer, the molar ratio of iron element to titanium element is 1:(300-650).
4. The perovskite solar cell according to claim 1 or 2, characterized in that: The transparent conductive layer includes FTO conductive glass.
5. A method for preparing a perovskite solar cell according to any one of claims 1 to 4, characterized in that: The following steps are involved: Applying a first mixed solution containing an organic titanium source, an iron source for forming the trivalent iron compound, and a first solvent on the transparent conductive layer to form a dense electron transport layer; Applying a second mixed solution containing an inorganic titanium source and a second solvent on the dense electron transport layer to form a mesoporous electron transport layer; A perovskite light absorption layer and a hole transport layer are sequentially formed on the mesoporous electron transport layer to obtain the perovskite solar cell.
6. The method for preparing a perovskite solar cell according to claim 5, characterized in that: Before applying the first mixed liquid on the transparent conductive layer, the transparent conductive layer is pretreated, and the pretreatment process includes: cleaning the transparent conductive layer with a cleaning agent, drying it, and then performing ultraviolet ozone treatment; wherein the cleaning agent includes one or more of water, acetone, isopropyl alcohol, ethanol, and glass cleaning agent.
7. The method for preparing a perovskite solar cell according to claim 5, characterized in that: The organic titanium source includes diisopropoxy diacetylacetonate titanium; and / or, the iron source comprises ferric acetylacetonate; and / or, the molar ratio of the iron element in the iron source to the titanium element in the organic titanium source is 1:(300-650); And / or, the first solvent comprises n-butanol.
8. The method for preparing a perovskite solar cell according to claim 5, characterized in that: The organic titanium source includes diisopropoxy diacetylacetonate titanium, the iron source includes ferric acetylacetonate, and the formation process of the first mixed liquid includes: mixing the diisopropoxy diacetylacetonate titanium and the ferric acetylacetonate, and then adding a first solvent to the obtained mixed liquid to obtain the first mixed liquid; wherein the volume ratio of the mixed liquid to the first solvent is 1:(14~18).
9. The method for preparing a perovskite solar cell according to any one of claims 5 to 8, characterized in that: The first mixed solution is spin-coated on the transparent conductive layer by a dynamic spin-coating method, and then annealed at 110-130° C. for 8-12 minutes to form the dense electron transport layer.
10. The method for preparing a perovskite solar cell according to claim 6, characterized in that: The inorganic titanium source includes titanium dioxide; and / or, the second solvent comprises ethanol; And / or, the second mixed solution is spin-coated on the dense electron transport layer by static spin coating, and then annealed at 450-550° C. for 40-70 min to form the mesoporous electron transport layer.
Citation Information
Patent Citations
Method for preparing nano-crystalline Fe-doped meso-porous TiO* thick film electrode
CN101567271A
Semiconductor electrode, preparation method thereof and solar cell comprising semiconductor electrode
CN101620939A
Ferroelectric enhanced solar cell and preparation method thereof
CN109698251A
Perovskite solar cell and preparation method thereof
CN112490367A
Iron containing hole blocking layer containing photoconductors
US20090035673A1